Inovasi Pembelajaran IPS untuk Meningkatkan Partisipasi Siswa dalam Kehidupan Sosial - Al Hafiz Rasya Ramadhan; Cyndy Felisya; Sani Safitri (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Innovation in social studies learning is essential to improve students' social participation. With the times and the increasing complexity of social issues, social studies learning should adopt new approaches that can help students understand social issues and be more involved in social activities. One such innovation is the use of more interactive learning approaches, such as project-based learning, case studies, and group discussions, as well as the use of digital technology to connect theoretical and applied knowledge. In addition to gaining knowledge about social issues, this innovation teaches students to think critically, work together, and act as agents of change in society. It is expected that learning that focuses on social experiences, both inside and outside the classroom, can enhance students' sense of social responsibility and encourage them to engage more actively and productively in social activities. This article emphasizes the important role of educators in creating a learning environment that encourages students to be actively and productively involved in their social lives. The goal of this learning is to produce a generation that is more socially aware, caring, and plays an active role in society.